ROS Robotics By Example - Fairchild, Carol; Fairchild, Carol; Harman, Dr. Thomas L. (Packt Publishing, 2016)
Bring life to your robot using ROS robotic applicationsAbout This BookThis book will help you boost your knowledge of ROS and give you advanced practical experience you can apply to your ROS robot platformsThis is the only book that offers you step-by-step instructions to solidify your ROS understanding and gain experience using ROS toolsFrom eminent authors, this book offers you a plethora of fun-filled examples to make your own quadcopter, turtlebot, and two-armed robotsWho This Book Is ForIf you are a robotics developer, whether a hobbyist, researchers or professional, and are interested in learning about ROS through a hands-on approach, then this book is for you. You are encouraged to have a working knowledge of GNU/Linux systems and Python.What You Will LearnGet to know the fundamentals of ROS and apply its concepts to real robot examplesControl a mobile robot to navigate autonomously in an environmentModel your robot designs using URDF and Xacro, and operate them in a ROS Gazebo simulationControl a 7 degree-of-freedom robot arm for visual servoingFly a quadcopter to autonomous waypointsGain working knowledge of ROS tools such as Gazebo, rviz, rqt, and Move-ItControl robots with mobile devices and controller boardsIn DetailThe visionaries who created ROS developed a framework for robotics centered on the commonality of robotic systems and exploited this commonality in ROS to expedite the development of future robotic systems.From the fundamental concepts to advanced practical experience, this book will provide you with an incremental knowledge of the ROS framework, the backbone of the robotics evolution. ROS standardizes many layers of robotics functionality from low-level device drivers to process control to message passing to software package management. This book provides step-by-step examples of mobile, armed, and flying robots, describing the ROS implementation as the basic model for other robots of these types. By controlling these robots, whether in simulation or in reality, you will use ROS to drive, move, and fly robots using ROS control.Style and approachThis is an easy-to-follow guide with hands-on examples of ROS robots, both real and in simulation.